The Influence of Career Development, Work Motivation, And Work Discipline On Employee Performance - Yustina Yasinta Bupu; Deni Wardani (Indonesia Banking School, 2024)
This study examines the effect of career development, work motivation, and work discipline on employee performance. Study on a permanent employee at the retail account services (RAS) division at the Bank X, South Jakarta. The independent variables in this study are Career Development, Work Motivation, and Work Discipline. At the same time, the dependent variable in this study is Employee Performance. Hypothesis testing in this study uses the PLS or Partial Least Square method with SmartPLS 3.0 software. The data collection technique used a Google form application questionnaire to collect respondent information. The sample in this study were all members of the population, which amounted to 70 permanent employees at the Bank X, South Jakarta. The analysis results show that Career Development has a positive and significant effect on Employee Performance. Work Motivation has a positive and significant effect on Employee Performance. Work Discipline has a positive and significant effect on Employee Performance.